1994
DOI: 10.1016/0732-8893(94)90086-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of detection methods for adenovirus from enteric clinical specimens

Abstract: Fecal samples submitted for virus examination over July 1990 to June 1991 from children < 3 years of age were examined by electron microscopy (EM), virus culture (VC), and enzyme immunoassay [EIA, group-reactive and adenovirus (Ad) 40/41 specific; Cambridge BioScience] to compare the detection rate of adenovirus from pediatric fecal specimens. Ad isolates of serotypes 1-7 grown in HEp-2 or primary rhesus monkey kidney cells were identified by neutralization. Graham 293 cell cultures were used only when specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Only in one study performed in Guatemala, it was reported that enteric adenovirus was seen 3 times more frequently than rotavirus and this has been linked to climate variations (5). Ahluwalia et al (6) stated that the prevalence of childhood gastroenteritis caused by adenovirus was 4.1%. In their studies done in our country by Gül et al (7), and Biçer et al (8), the incidence of gastroenteritis caused by adenovirus was found to be 4.7% and 16.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Only in one study performed in Guatemala, it was reported that enteric adenovirus was seen 3 times more frequently than rotavirus and this has been linked to climate variations (5). Ahluwalia et al (6) stated that the prevalence of childhood gastroenteritis caused by adenovirus was 4.1%. In their studies done in our country by Gül et al (7), and Biçer et al (8), the incidence of gastroenteritis caused by adenovirus was found to be 4.7% and 16.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Direct immunofluorescence and electron microscopy of respiratory secretion or tissue samples may be used to diagnose end-organ involvement [3]. Rapid testing of ocular, respiratory, and stool specimens may be performed with commercially available EIAs, although the sensitivity of these tests is limited [59].…”
Section: Diagnosis and Monitoringmentioning
confidence: 99%
“…Değişik ülkelerde yapılan çalışmalarda adenovirusların viral gastroenterit olgularının %2.4-22.2'sinden sorumlu olduğu bildirilirken (25)(26)(27)(28)30,31), bu oran rotaviruslar için %11-71 olarak saptanmıştır (28,29).…”
Section: İrdelemeunclassified